2021
DOI: 10.1097/md.0000000000025403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perinatal HIV-infection on the cortical thickness and subcortical gray matter volumes in young adulthood

Abstract: Brain atrophy has been observed in perinatally HIV-infected patients (PHIV) despite initiation on combined antiretroviral treatment (cART), but neuroimaging studies are limited. We aimed to evaluate cortical thickness (CT) and subcortical gray matter (GM) volumes of PHIV youths with stable immunovirological situation and with a normal daily performance. A prospective cross-sectional study was conducted. A total of 25 PHIV patients on cART and 25 HIV-negative (HIV-) controls matched by age, sex, leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Several recent papers have focused on structural measures such as cortical thickness, surface area, and gyrification [ 62 , 65 •, 66 ] that have increasingly been used in studies of HIV among children [ 67 ], as well as adults [ 68 – 72 ], and are sensitive to developmental processes. The few studies focusing on adolescents and young adults show regionally specific decreases in cortical thickness, including temporal, orbitofrontal, and occipital lobes in combination with lower gray matter volume in subcortical structures among Spanish young adults [ 62 ], decreased cortical thickness in right temporal lobe and fusiform gyrus among Zambian adolescents with PHIV [ 73 ], and increased thickness in left occipital and right olfactory areas and decreased cortical thickness in temporal and orbitofrontal regions among Chinese youth [ 60 ]. Lewis and colleagues described decreased cortical thickness, surface area, and gyrification in frontal, parietal, and temporal regions among the US adolescents with PHIV compared to an age-matched PING cohort; the distribution of differences varied across the three metrics, which reflect different developmental processes [ 65 •].…”
Section: Selected Recent Neuroimaging Studies Among Adolescents and Y...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent papers have focused on structural measures such as cortical thickness, surface area, and gyrification [ 62 , 65 •, 66 ] that have increasingly been used in studies of HIV among children [ 67 ], as well as adults [ 68 – 72 ], and are sensitive to developmental processes. The few studies focusing on adolescents and young adults show regionally specific decreases in cortical thickness, including temporal, orbitofrontal, and occipital lobes in combination with lower gray matter volume in subcortical structures among Spanish young adults [ 62 ], decreased cortical thickness in right temporal lobe and fusiform gyrus among Zambian adolescents with PHIV [ 73 ], and increased thickness in left occipital and right olfactory areas and decreased cortical thickness in temporal and orbitofrontal regions among Chinese youth [ 60 ]. Lewis and colleagues described decreased cortical thickness, surface area, and gyrification in frontal, parietal, and temporal regions among the US adolescents with PHIV compared to an age-matched PING cohort; the distribution of differences varied across the three metrics, which reflect different developmental processes [ 65 •].…”
Section: Selected Recent Neuroimaging Studies Among Adolescents and Y...mentioning
confidence: 99%
“…The majority of recent studies address brain structural findings by comparing youth with PHIV to age-matched youth without HIV infection [58][59][60][61][62] or to large normative databases [63, 64, 65•]. These studies have noted differences in white matter integrity [61,66] and cortical and subcortical gray and white matter volume that are associated with performance on cognitive measures [58][59][60]64] and markers of systemic inflammation [66], and differences in white matter microstructure using DTI [61].…”
Section: Selected Recent Neuroimaging Studies Among Adolescents and Y...mentioning
confidence: 99%
“…The FDA has cleared this combination of monoclonal antibodies to SARS-COV-2 on an emergency basis (REGEN-COV) for co-administration by intravenous or subcutaneous injection for the treatment of mild to moderate COVID-19 in individuals over 12 years of age and weighing no less than 40 kg who are at high risk for progression to severe COVID-19 [61,62]. Traditional risk groups would also include overweight patients or pregnant women, as well as those suffering from cardiovascular disease, hypertension or chronic respiratory disease (Table 1) [61,63,64].…”
Section: Casirivimab + Imdevimabmentioning
confidence: 99%
“…HIV-infected children who are now young adults received cART after the first few years of life and thus neurocognitive impairment has been observed, but with good performance in daily life. Some neuroimaging studies have shown alterations in patients with good neurological function [61].…”
Section: Have We Ended Vertical Transmission? Jose Tomás Ramosmentioning
confidence: 99%
“…This has allowed HIV infected women to carry pregnancies with greatly reduced risk of PHIV transmission, and for children who acquired HIV perinatally to grow into adulthood with improved life expectancy and quality of life without major chronic comorbidities. However, significant neurological and neurocognitive complications persist in the brains of PHIV children and young adults despite the use of ART (Uban et al, 2015;Hoare et al, 2018;Sarma et al, 2019Sarma et al, , 2021Thakur et al, 2019;Van den Hof et al, 2019;Martin-Bejarano et al, 2021;Ruiz-Saez et al, 2021;Nichols, 2022). Extensive clinical studies in adult HIV patients indicated that most antiretrovirals either have poor penetration across the blood-brain barrier (BBB) or are effectively removed from the brain parenchyma, reducing their efficacy in suppressing HIV viral replication (Mzingwane and Tiemessen, 2017;Osborne et al, 2020).…”
Section: Introductionmentioning
confidence: 99%